PENGARUH KOMITE AUDIT, KOMPOSISI DEWAN KOMISARIS, DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - ANGGARA, MUHAMAD BAYU; KURNIADI, EDRIC (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
Research on earnings management aims to obtain empirical evidence regarding the effect of audit committee, composition of commissioners, company growth, leverage, company size, company age, institutional ownership, managerial ownership, and audit quality on earnings management in non-financial companies in Indonesia. The population of this study were non-financial companies listed on the Indonesia Stock Exchange from 2016 to 2019. There are 131 companies selected as samples using purposive sampling method. The sample was processed and tested using multiple regression methods to analyze data and using discretionary accruals calculated using the modified jones model with SPSS 25 application. The results of this study indicate that the audit committee, composition of commissioners, firm size, firm age, managerial ownership and audit quality do not have a significant effect on earnings management, while company growth, leverage and institutional ownership have an influence on earnings management